MEDICAL STUDENTS' KNOWLEDGE OF THE CHARACTERISTIC FEATURES AND PREVENTION OF TUBERCULOSIS - B. Yustiniyanova; Gabriela Tsankova (Peytchinski Publishing, 2010)
Medical students' knowledge of the main characteristic features of tuberculosis and the prevention of the disease was studied by means of an anonymous inquiry examination of 84 students of the Medical College of Varna during the 2009/2010 academic year. They presented with good knowledge of the main characteristics of tuberculosis such as predisposing factors, risk groups, source and mechanism of transmission of the infection. They were better grounded in the common preventive measures for avoiding the tuberculosis infection rather than in those towards the contact persons. Most respondents indicated the role of Mantoux test (61%) and microbiological examination of sputum.